Construction Law for the Crime of Sexual Harassment in Indonesia: Beyond the Basics of Criminal Law - Novita Erdianti, Ratri; Wasis; Anggraeny, Isdian; Kagiso Hlongwane (JUSTITIA JURNAL HUKUM, 2024)
Sexual Harassment in Indonesian is defined as sexual harassment, which often occurs in society. This kind of condition can be carried out by the community directly or indirectly, physically or verbally, towards the victim. Sexual harassment is an act of a sexual nature that makes the victim feel uncomfortable and disadvantaged, so legal action needs to be taken to take action against the perpetrator. Because there are so many forms of sexual harassment, it seems necessary to examine which acts of sexual harassment qualify as criminal acts according to positive criminal law in Indonesia. In this research, the formulation of the problem raised concerns about how the legal construction of sexual harassment is in criminal law in Indonesia. This research uses a normative juridical method that will analyze acts of sexual harassment that are associated with elements of criminal acts based on criminal law in Indonesia, both based on the Criminal Code and in connection with other related laws and regulations.